The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/andr.12769
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diagnosis and sperm retrieval outcomes for Chinese patients with congenital bilateral absence of vas deferens

Abstract: Background Congenital bilateral absence of the vas deferens (CBAVD) is a frequent cause of obstructive azoospermia. CBAVD is mainly caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene and is also related to the X‐linked ADGRG2 (adhesion G protein‐coupled receptor G2) gene. Genetic screening and counseling strategies for Chinese CBAVD populations remain controversial because the genetic background of CBAVD in Chinese population is largely unknown. Objectives In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…The 5T allele polymorphism varies considerably by geographic location and ethnicity, particularly among non-Caucasian populations ( Dork et al, 1997 ). In the current study, the frequency of the 5T allele was the most frequent variant, similar to other reports in Chinese cohorts ( Du et al, 2014 ; Gaikwad et al, 2018 ; Wang et al, 2020 ). No ADGRG2 variants were identified, suggesting ADGRG2 variants may not play a major role in these CAVD populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 5T allele polymorphism varies considerably by geographic location and ethnicity, particularly among non-Caucasian populations ( Dork et al, 1997 ). In the current study, the frequency of the 5T allele was the most frequent variant, similar to other reports in Chinese cohorts ( Du et al, 2014 ; Gaikwad et al, 2018 ; Wang et al, 2020 ). No ADGRG2 variants were identified, suggesting ADGRG2 variants may not play a major role in these CAVD populations.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 29 out of 50 (58%) patients had at least one reportable CFTR variant. These results demonstrated that our CAVD population had a lower percentage than previous reports in which 70%-80% of CBAVD patients carried at least one CFTR mutation (Yu et al, 2012;Wang et al, 2020), which may be due to our small sample size. The variant c.1521_1523delCTT (F508del) is one of the most common variants in northern European CAVD populations, accounting for up to one-third of CAVD patients (Barratt et al, 2017;Bieth et al, 2021), whereas only two (2/50) are carriers in our CAVD patients.…”
Section: Discussioncontrasting
confidence: 60%
“…Recent research reported that among 263 Chinese patients with CBAVD, 5 (1.9%) patients were detected for copy number variants in the region of the CFTR gene (four of them carried partial deletions and one carried partial duplication of CFTR ), 37 but other studies did not find copy number variations of CFTR in males with CBAVD. 38 , 39 A larger number of samples and more sensitive gene detection methods are essential for further research. Although a specific knock-in mouse model supported our findings, further investigations are needed to clarify the function of CFTR in spermatogenesis in animal models in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests the presence of a mixed pathology, with both obstructive damage and testicular failure. PESA outcomes justify these; both in terms of activity or vitality were low and abnormality rates were high [25].…”
Section: F I G 2 Fertility Outcomes In Icsi Cycles In Couples With Cbavdmentioning
confidence: 90%